Continuous Wavelet Transform for Bearing Damage Detection in Electric Motors - Ayaz, E.; Ozturk, A.; Seker, S. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
The purpose of this paper is to extract features from vibration signals measured from induction motors subjected to accelerated bearing fluting aging. The signals taken from accelerometers placed near to process end bearing were first combined using simple sensor fusion method and then spectral analysis and time-scale analysis were performed. Fused vibration signals were decomposed into several scales using continuous wavelet transform analysis and selected scales was further investigated to get detailed information relating to bearing damage features. And also the advantage of the continuous wavelet transform over short time Fourier transform was emphasized in terms of getting the bearing damage between 2-4 kHz